What Kaplan-Meier Survival Curves Don’t Tell Us About CNS Disease - Miller, Katelyn D. (J Neuroimmunol, 2017)
Central nervous system consequences of viral infections are rare, but when they do occur, they are often serious and clinically challenging to manage. Our awareness of the perils of neuroinvasion by viruses is growing: the recently appreciated impact of Ebola and Zika virus infections on CNS integrity, decreases in vaccination coverage for potentially neurotropic viruses such as measles, and increased neurovirulence of some influenza strains collectively highlight the need for a better understanding of the viral-neural interaction. Defining these interactions and how they result in neuropathogenesis is paramount for the development of better clinical strategies, especially given the limited treatment options that are available due to the unique physiology of the brain that limits migration of blood-borne molecules into the CNS parenchyma. In this perspective, we discuss some unique aspects of neuronal viral infections and immune-mediated control that impact the pathogenic outcomes of these infections. Further, we draw attention to an often overlooked aspect of neuropathogenesis research: that lack of overt disease, which is often equated with survival post-infection, likely only scratches the surface of the myriad ways by which neurotropic infections can impair CNS function.